MOBILE APPLICATION FOR TEACHING AND ASSESSING STUDENTS NEEDING ADDITIONAL CURRICULAR SUPPORT (SNACS) IN DENTAL EDUCATION - Manivasakan, Shivasakthy; Thangamuthu , Pradeep; Raman, Sethuraman K; Manivasakan, Kanchana (International Journal of Psychosocial Rehabilitation, 2020)
The current web 2.0 generation of students are having more technological literacy than their subject literacy. Development of innovative mobile application with different teacher and student interface for teaching and assessment is not much studied in dental education.The basic requirements needed for a mobile application to be used by the students and the teachers were chosen. The teacher interface was enabled to create and send short study material, assignments and objective type tests. The students’ interface was enabled to receive the notifications and answer the objective tests. The teacher would be able to monitor the individual progress of all the enrolled students. The first year undergraduate dental students from a private dental college enrolled and used the app with a mentor on teacher interface. Qualitative analysis of the efficacy of mobile application was studied using questionnaire and focus group discussion. The mobile application “SNACS” was successfully devised. The students used the application for that academic year and gave a positive feedback. The app was found to be more user-friendly and improved the academic performance of the students. It helped them to change their study habits positively.Within the limitations of the study, the mobile application “SNACS” was working effectively in the android mobiles and it helped the Students Needing Additional Curricular Support to improve their academic performance.